2020
DOI: 10.3329/bjms.v19i0.48166
|View full text |Cite
|
Sign up to set email alerts
|

Ibn Tofail’sUniversity students’ satisfaction evaluation towards distance learning and its impacts on the students’ mental health during the Covid 19 Confinement.

Abstract: Aims, objectives and methods: The study we have conducted aims to evaluate Moroccan students’ satisfaction level with regard to the use of distance learning platforms during the Covid 19 confinement period. We also attempt to examine the impact of distance learning on the students’ mental health.Our research has demonstrated that imposing distance learning as a learning process to students produces a substantial stress level within 49% of the investigated student population.Indeed, the students’ full immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…We excluded 63 articles and therefore retrieved and appraised the 20 lasting articles based on their full-texts and also considering our selection criteria. Finally, 12 articles [24][25][26][27][28][29][30][31][32][33][34][35] were systematically reviewed and qualitatively summarized. The PRISMA flow chart showing our study selection process is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We excluded 63 articles and therefore retrieved and appraised the 20 lasting articles based on their full-texts and also considering our selection criteria. Finally, 12 articles [24][25][26][27][28][29][30][31][32][33][34][35] were systematically reviewed and qualitatively summarized. The PRISMA flow chart showing our study selection process is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 12 studies were realized in seven countries, namely Ethiopia (n = 4), Egypt (n = 2), Morocco (n = 2), Liberia (n = 1), Libya (n = 1), Sudan (n = 1) and Tunisia (n = 1). Amid selected studies, 11 were reported as cross-sectional studies, and one as a transversal descriptive study [33]. Data were collected exclusively electronically (online surveys) in 9/12 studies, only with a paper version form in one study [32], both with online and paper forms in one study [29], and through phone calls in one study [26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure has had serious implications on higher education in the country as it resulted in the disruption of the educational sector and discontinuity of all educational levels. Faculties of pharmacy in the country were not an exception, with a suspension of both presential courses alongside clinical rotations to minimize the incidence of pharmacy students' exposition to COVID-19 transmission [5].…”
mentioning
confidence: 99%